ANALISIS ASPEK BIOFISIK DALAM PENILAIAN KERAWANAN BANJIR DI SUB DAS SAMIN PROVINSI JAWA TENGAH - Wiwin Budiarti; Evi Gravitiani; Mujiyo Mujiyo (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Floods a main problem in Samin sub watershed, which is part of the Bengawan Solo watershed, Central Java Province. Assessment of the flood vulnerability level and its determinant causes is required as a basis information for policy makers to design a flood mitigation strategy. This study aims to assess the level of flood vulnerability and to analyze the biophysical aspects that caused flooding in Samin sub watershed. The method used is survey and the quantitative analysis of biophysical aspects including slope, soil, drainage density, land use and rainfall using map-overlay and scoring approach. Data analysis using Geographic Information System (GIS) technology. The results showed that the Samin sub-watershed areas has five levels of flood vulnerability is the category of